Models - Wartofsky, Marx W. author. aut Link
XXVI, 398 p.
Keywords: Marx Wartofsky has been working for many years within an unusual confluence of philosophical problems. He brings to these intersecting problems his comprehensive intelligence, at once imaginative and rigorous, analytic and historical. He is a philosopher's philosopher, but also Everyman's. Wartofsky is philosopher of the natural and the social sciences, of perception, esthetics and the creative arts, of the 18th century French and the 19th century Germans, of politics and morality, ofthe methods and morals of medicine, and it is plain, of all human existence. To a colleague, he seems Jack-of-all-philosophical-trades, and master of them too. The reader soon will learn that Wartofsky is a genial, lucid and relaxed philosophical companion, deeply serious but without noticeable anxiety. I need not highlight these selected epistemological papers gathered as, and about, Models, since Wartofsky's own introductory remarks are helpful and stimulating in that respect. I need only, after 21 years of friendship and collaboration with him, warn the reader to beware of how profound and provocative these papers will show themselves to be beneath their good-humored and swiftly-flowing surface. And I must publicly note the pleasure with which I welcome Marx Wartofsky's volume to our Boston Studies. Boston University R.S.C. Center for the Philosophy and History of Science September 1979 vii TABLE OF CONTENTS EDITORIAL PREFACE VII xi AC K NOWLEDGEMENTS xiii INTRODUCTION The Model Muddle: Proposals for an Immodest Realism 1.